Battery and electronic equipment

CN119547233APending Publication Date: 2025-02-28ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380014447.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

How to reduce the impedance of semi-solid-state batteries and improve their cycle performance.

Method used

Electrolytes are prepared by using a specific ratio of functional additives and polymer monomers, and an SEI film is formed by a low-temperature formation method to improve the battery interface, reduce impedance, and improve cycle performance.

Benefits of technology

It effectively reduces battery impedance, improves battery cycle performance and conductivity, and enhances battery rate performance and temperature characteristics.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a battery and electronic equipment. A first aspect of the present application provides a battery comprising an electrolyte; injecting dimethyl carbonate into the battery, standing for 36 hours, sampling, and carrying out gas chromatographic analysis on liquid in the battery; based on the capacity of the battery, the liquid injection amount of the dimethyl carbonate is not less than 2.5 g / Ah; a first characteristic peak exists at the position of 3.65-4.50 min, and a second characteristic peak exists at the position of 4.95-6.50 min. According to the battery provided by the invention, the first functional auxiliary agent with the appearance time of 3.65-4.50 min and the second functional auxiliary agent with the appearance time of 4.95-6.50 min are detected in the residual components of the electrolyte, and the first functional auxiliary agent and the second functional auxiliary agent can continuously exist, so that the battery interface can be improved, the impedance of the battery can be reduced, and the cycle performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Battery and electronic device Technical Field

[0001] The present application belongs to the field of batteries and relates to a battery and an electronic device. Background Art

[0002] With the rapid development of new energy, lithium-ion batteries are in urgent need of high energy density and superior safety. Compared to traditional liquid batteries, semi-solid and solid-state batteries offer higher energy density and longer battery life, offering broader application prospects in cutting-edge consumer electronics, electric vehicles, energy storage devices, and other new energy fields.

[0003] Semi-solid-state and solid-state batteries differ from liquid-state batteries in their electrolytes. Semi-solid-state batteries use semi-solid electrolytes, solid-state batteries use solid electrolytes, and liquid-state batteries use liquid electrolytes. Compared to liquid-state batteries, semi-solid-state and solid-state batteries have higher impedance and lower cycle performance. Therefore, reducing the impedance of semi-solid-state batteries and improving their cycle performance are pressing technical challenges facing those skilled in the art.

[0004] Summary of the Invention

[0005] The present application provides a battery, including an electrolyte, which helps to reduce the impedance of the battery and improve its cycle performance.

[0006] The present application also provides an electronic device comprising the above-mentioned battery.

[0007] A first aspect of the present application provides a battery, comprising an electrolyte;

[0008] The battery was sealed after injecting dimethyl carbonate and allowed to stand for 36 hours, and then the mixed liquid components inside the battery were taken out and analyzed by gas chromatography.

[0009] Based on the capacity of the battery, the injection amount of dimethyl carbonate is not less than 2.5g / Ah;

[0010] In the gas chromatography analysis spectrum, there is a first characteristic peak at 3.65-4.50 min, and a second characteristic peak at 4.95-6.50 min.

[0011] The battery as described above has a first characteristic peak at 3.65-4.50 min and a second characteristic peak at 4.95-6.50 min in a gas chromatography analysis spectrum.

[0012] In the battery as described above, the ratio of the peak area of ​​the second characteristic peak to the peak area of ​​the first characteristic peak is greater than 1.

[0013] In the battery as described above, the ratio of the peak area of ​​the second characteristic peak to the peak area of ​​the first characteristic peak is not greater than 3.2.

[0014] The battery as described above, wherein the electrolyte has M first diffraction peaks with a 2θ diffraction angle of x and N second diffraction peaks with a 2θ diffraction angle of y in an X-ray diffraction pattern, M ≥ 1, N ≥ 1;

[0015] Among them, 10°≤x≤30°, 30°≤y≤50°;

[0016] The sum of the half-peak widths of the M first diffraction peaks is a, and the sum of the half-peak widths of the N second diffraction peaks is b, wherein 1.1≤b / a≤3.2.

[0017] For the battery as described above, 1.1≤b / a≤1.5;

[0018] Or, 2.1≤b / a≤2.3.

[0019] For the battery as described above, 1.1≤a≤1.5, and 1.4≤b≤3.6.

[0020] The battery as described above, wherein the conductivity of the electrolyte is 4mS / cm-12mS / cm;

[0021] Preferably, the conductivity of the electrolyte is 5 mS / cm-12 mS / cm.

[0022] In the battery as described above, the electrolyte includes a polymer obtained by polymerizing a monomer, the monomer includes a functional group, and the functional group includes at least two acrylate groups.

[0023] In the battery as described above, the polymerizable monomer is selected from one or more of a bifunctional monomer, a trifunctional monomer, a tetrafunctional monomer, and a hexafunctional monomer.

[0024] In the battery as described above, the bifunctional monomer is one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, and ethoxylated bisphenol A diacrylate and its derivatives;

[0025] and / or the trifunctional monomer is one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, and trimethylolpropane trimethacrylate and its derivatives;

[0026] and / or, the tetrafunctional monomer is ethoxylated (5) pentaerythritol tetraacrylate and its derivatives;

[0027] And / or, the hexafunctional monomer is dipentaerythritol hexaacrylate and its derivatives.

[0028] The battery as described above is prepared by a method comprising the following steps:

[0029] The battery comprising the electrolyte precursor solution is charged to 3.7V at a temperature of 10°C to 40°C, a pressure of ≤3 MPa, and a rate of ≤0.3C; subsequently, the battery is charged to a cut-off voltage of ≥4.0V at a temperature of 60°C to 90°C, a pressure of ≤3 MPa, and a rate of ≤0.9C, to obtain the battery;

[0030] The electrolyte precursor solution includes polymerizable monomers.

[0031] The battery as described above is a solid-state battery or a semi-solid-state battery.

[0032] In the battery as described above, the electrolyte is a solid electrolyte or a semi-solid electrolyte.

[0033] The battery as described above is a semi-solid-state battery, and the electrolyte includes a polymer and an electrolyte solution.

[0034] In the battery as described above, the electrolyte comprises 0.5 wt% to 10 wt% of a polymer and 90 wt% to 99.5 wt% of an electrolyte solution.

[0035] In the battery as described above, the electrolyte includes a lithium salt and a non-aqueous organic solvent.

[0036] The battery as described above, wherein the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bisfluorooxalatoborate, lithium bisfluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium difluorophosphate, lithium perchlorate, lithium bisfluorosulfonamide and lithium bistrifluoromethylsulfonyl imide;

[0037] And / or, the non-aqueous organic solvent is selected from one or more of cyclic carbonates, linear carbonates, and linear carboxylates.

[0038] The battery as described above also includes a positive electrode sheet; the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution positive electrode material, lithium nickel cobalt oxide, lithium nickel titanium magnesium oxide, lithium nickel oxide, spinel lithium manganese oxide, nickel cobalt tungsten, lithium nickel manganese oxide, and sodium-containing lithium cobalt oxide.

[0039] The battery as described above also includes a negative electrode sheet; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes one or more of silicon, silicon carbon, SiOx, lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerene, graphene, coke, carbon fiber, boron and its derivatives, aluminum and its derivatives, magnesium and its derivatives, bismuth and its derivatives, nickel and its derivatives, silver and its derivatives, zinc and its derivatives, titanium and its derivatives, gallium and its derivatives, indium and its derivatives, tin and its derivatives, lithium nitride, and copper nitride.

[0040] A second aspect of the present application provides an electronic device comprising any of the above-mentioned batteries.

[0041] In the battery provided in the present application, a first functional auxiliary agent with a peak time of 3.65-4.50 min and a second functional auxiliary agent with a peak time of 4.95-6.50 min are detected in the residual components of the electrolyte, and the first functional auxiliary agent and the second functional auxiliary agent can exist continuously, which helps to improve the battery interface, reduce the impedance of the battery, and improve its cycle performance. DETAILED DESCRIPTION

[0042] To make the purpose, technical solutions, and advantages of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0043] The present application provides a battery, comprising an electrolyte;

[0044] Dimethyl carbonate was injected into the battery, and after standing for 36 hours, a sample was taken and the liquid in the battery was analyzed by gas chromatography;

[0045] Based on the capacity of the battery, the injection amount of dimethyl carbonate is not less than 2.5g / Ah;

[0046] In the gas chromatography analysis spectrum, there is a first characteristic peak at 3.65-4.50 min, and a second characteristic peak at 4.95-6.50 min.

[0047] The battery provided in the present application includes an electrolyte, and a first functional auxiliary agent with a peak time of 3.65-4.50 min and a second functional auxiliary agent with a peak time of 4.95-6.50 min are detected in the battery components, and the first functional auxiliary agent and the second functional auxiliary agent can exist continuously, improve the battery interface, reduce the impedance of the battery, and improve its cycle performance.

[0048] Furthermore, in the gas chromatography analysis spectrum, there is a first characteristic peak at 3.70-4.20 min, and a second characteristic peak at 5.00-6.20 min.

[0049] Furthermore, in the gas chromatography analysis spectrum, there is a first characteristic peak at 3.80-3.90 min, and a second characteristic peak at 5.40-5.50 min.

[0050] In a specific embodiment, the ratio of the peak area of ​​the second characteristic peak to the first characteristic peak is greater than 1. When the peak area ratio of the two is greater than 1, it helps to optimize the ratio of the first functional additive to the second functional additive, further improve the battery interface, and reduce the battery impedance.

[0051] Furthermore, the ratio of the peak area of ​​the second characteristic peak to the peak area of ​​the first characteristic peak is generally not greater than 3.2.

[0052] It can be understood that in the gas chromatography analysis spectrum, the first characteristic peak / second characteristic peak can include one or more, as long as they meet the peak time. When any one of the first characteristic peak and the second characteristic peak includes at least two, the peak areas of the characteristic peaks that meet the peak time are added to obtain the peak areas of the second characteristic peak and the first characteristic peak.

[0053] In a specific embodiment, the electrolyte has M first diffraction peaks with a 2θ diffraction angle of x and N second diffraction peaks with a 2θ diffraction angle of y in its X-ray diffraction pattern, where M≥1 and N≥1;

[0054] Among them, 10°≤x≤30°, 30°≤y≤50°;

[0055] The sum of the half-peak widths of the M first diffraction peaks is a, and the sum of the half-peak widths of the N second diffraction peaks is b, wherein 1.1≤b / a≤3.2.

[0056] Research has found that when the electrolyte is subjected to X-ray diffraction analysis, at least one first diffraction peak with a 2θ diffraction angle in the range of 10° to 30° and at least one second diffraction peak with a 2θ diffraction angle in the range of 30° to 50° will appear on the X-ray diffraction pattern, and the ratio of the sum of the half-peak widths of all second diffraction peaks to the sum of the half-peak widths of all first diffraction peaks is in the range of 1.1 to 3.2, indicating that the electrolyte has special crystallization properties, which is conducive to the conduction of lithium ions in the electrolyte, thereby making the electrolyte have good electrical conductivity, reducing the impedance of the battery, and further improving the cycle performance of the battery.

[0057] It's important to note that when performing X-ray diffraction analysis on electrolytes, especially those in batteries, the electrolytes must be pretreated after disassembly to remove other components. This pretreatment involves washing the electrolyte with deionized water, vacuuming it at 80°C for 48 hours, and testing for a moisture content of less than 1000 ppm before performing X-ray diffraction analysis.

[0058] In a specific embodiment, 1.1≤b / a≤1.5; or, 2.1≤b / a≤2.3.

[0059] Furthermore, when 1.1≤a≤1.5 and 1.4≤b≤3.6, it is more conducive to improving the electrolyte conductivity, thereby making the battery have better rate performance and temperature characteristics.

[0060] Furthermore, the conductivity of the electrolyte can reach 4mS / cm-12mS / cm, further, the conductivity of the electrolyte can reach 5mS / cm-12mS / cm, further, the conductivity of the electrolyte can reach 7mS / cm-12mS / cm.

[0061] In a specific embodiment, the electrolyte includes a polymer obtained by polymerizing a polymerized monomer, the polymerized monomer includes a functional group, and the functional group includes at least two acrylate groups.

[0062] Furthermore, the polymerizable monomer is selected from one or more of a difunctional monomer, a trifunctional monomer, a tetrafunctional monomer, and a hexafunctional monomer.

[0063] Specifically, the difunctional monomer refers to a polymer monomer containing two carbon-carbon double bonds, including but not limited to one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, and ethoxylated bisphenol A diacrylate and its derivatives.

[0064] The trifunctional monomer refers to a polymer monomer containing three carbon-carbon double bonds, including but not limited to one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, and trimethylolpropane trimethacrylate and its derivatives.

[0065] The tetrafunctional monomer is ethoxylated (5) pentaerythritol tetraacrylate and its derivatives;

[0066] The hexafunctional monomer is dipentaerythritol hexaacrylate and its derivatives.

[0067] It should be noted that the above-mentioned derivatives refer to products obtained by replacing the original groups in the main body with new substituent groups. For example, the derivatives of ethoxylated trimethylolpropane triacrylate refer to products obtained by replacing the original groups (e.g., hydrogen atoms) in ethoxylated trimethylolpropane triacrylate with substituent groups. The present invention is not limited to the specific choice of substituent groups, and for example, the substituent groups can be at least one of halogen atoms, hydroxyl groups, thiol groups, nitro groups, cyano groups, isocyano groups, sulfone groups, hydroxylamine groups, carboxyl groups, carbonyl groups, aromatic hydrocarbons, heteroaromatic hydrocarbons, heterocycloalkyl groups, amino groups, alkoxy groups, aromatic ring oxygen groups, aromatic heterocyclooxy groups, amide groups, alkylthio groups, aromatic ring sulfur groups, heteroaromatic ring sulfur groups, silicon groups, boron groups, etc.

[0068] In one embodiment, the battery is prepared by a method comprising the following steps:

[0069] The battery comprising the electrolyte precursor solution is charged to 3.7V at a temperature of 10°C to 40°C, a pressure of ≤3MPa, and a rate of ≤0.3C; subsequently, the battery is charged to a cut-off voltage of ≥4.0V at a temperature of 60°C to 90°C, a pressure of ≤3MPa, and a rate of ≤0.9C, to obtain the battery;

[0070] The electrolyte precursor solution includes polymerizable monomers.

[0071] The present application adopts a low-temperature chemical formation method, so that the polymerized monomer participates in the formation of the SEI film while polymerizing and curing, which helps to improve the residual components of the electrolyte in the battery. A first functional additive with a peak time of 3.65-4.50min and a second functional additive with a peak time of 4.95-6.50min are detected in the residual components of the battery, and the first functional additive and the second functional additive can continue to exist, improving the battery interface, reducing the impedance of the battery, and improving its cycle performance.

[0072] It can be understood that the electrolyte precursor solution also includes an initiator for initiating the polymerization of the polymerization monomer, and the initiator is selected from one or more of benzoyl peroxide and its derivatives, tert-butyl peroxyethyl octanoate and its derivatives, diisopropyl peroxide and its derivatives, tert-butyl peroxybenzoate and its derivatives, tert-butyl peroxybutyl pentanoate and its derivatives, diisopropyl peroxydicarbonate and its derivatives, cyclohexanone peroxide and its derivatives, and methyl ethyl ketone peroxide and its derivatives.

[0073] In a specific embodiment, the battery provided in the present application is a solid-state battery or a semi-solid-state battery, and the electrolyte is a solid-state electrolyte or a semi-solid-state electrolyte.

[0074] When the battery is a semi-solid battery, it includes a semi-solid electrolyte including a polymer and an electrolyte solution.

[0075] Furthermore, the semi-solid electrolyte includes 0.5 wt% to 10 wt% of a polymer and 90 wt% to 99.5 wt% of an electrolyte.

[0076] In one embodiment, the electrolyte includes a lithium salt and a non-aqueous organic solvent.

[0077] The lithium salt can be selected from the electrolyte lithium salts commonly used in the art, including but not limited to one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bisfluorooxalatoborate, lithium bisfluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium difluorophosphate, lithium perchlorate, lithium bisfluorosulfonamide and lithium bistrifluoromethylsulfonyl imide.

[0078] The non-aqueous organic solvent may be an organic solvent commonly used in the art that can dissolve lithium salts, specifically one or more selected from cyclic carbonates, linear carbonates, and linear carboxylates.

[0079] Among them, the cyclic carbonate is selected from one or more of ethylene carbonate and propylene carbonate, the linear carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, and the linear carboxylic acid ester is selected from at least one of ethyl propionate, propyl propionate and propyl acetate.

[0080] In a specific embodiment, the mass content of the cyclic carbonate in the non-aqueous organic solvent is 20-60 wt %, and the mass content of the linear carbonate and / or linear carbonate is 40-80 wt %.

[0081] In addition, the electrolyte also includes additives, which are selected from one or more of vinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, vinyl sulfate, 1,3-propylene sultone, lithium difluorophosphate, lithium bis(oxalatoborate), fluoroalkyl phosphate, 2-oxo-1,3,2-dioxathiapentane, ethylene carbonate, propylene carbonate, and 1,3,6-hexanetrinitrile.

[0082] The battery of the present application, in addition to the electrolyte, also includes a positive electrode sheet, a negative electrode sheet and a separator.

[0083] Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer arranged on the surface of the positive electrode current collector. The positive electrode current collector can be selected from positive electrode current collectors commonly used in the art, such as aluminum foil. The positive electrode active material layer includes a positive electrode active material, a conductive agent, a binder and an additive. The positive electrode active material can be selected from lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (LiCoO2), lithium phosphate (LiFePO4), lithium phosphate ... z Ni x Coy Mn 1-x-y O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, 0 < x + y < 1), lithium manganate (LiMnO2), lithium nickel cobalt aluminate (Li z Ni x Co y Al 1-x-y O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, 0.8 ≤ x + y < 1), lithium nickel cobalt manganese aluminate (Li z Ni x Co y Mn w Al 1-x-y-w O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, w > 0, 0.8 ≤ x + y + w < 1), nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution cathode material (xLi2MnO3·(1 - x)LiMO2, where M = Ni / Co / Mn), lithium nickel cobaltate (LiNi x Co y O2, where x > 0, y > 0, x + y = 1), lithium nickel titanium magnesium oxide (LiNi x Ti y Mg z O2, where, x > 0, y > 0, z > 0, x + y + z = 1), lithium nickel oxide (Li2NiO2), spinel lithium manganate (LiMn2O4), nickel cobalt tungsten, lithium nickel manganate, sodium-containing lithium cobaltate (Li n1-y1 Na y1 Co 1-a1-b1 M1 b1 M2 a1 O2 or Li n2-y2-b2 Na y2 Co 1- a2 M1 b2 M2 a2 O2, 0.6 ≤ n1 ≤ 0.8, 0 < y1 ≤ 0.05, 0 ≤ a1 ≤ 0.1, 0 < b1 ≤ 0.1, 0 < b1 / (1 - a1 - b1) < 0.1; 0.6 ≤ n2 ≤ 0.8, 0 < y2 ≤ 0.05, 0 ≤ a2 ≤ 0.1, 0 < b2 ≤ 0.02; M1 is selected from at least one of Te, W, Al, B, P, and K; M2 is a doping element different from M1 such as Mg, Zr, Y, La, Ni, etc.).

[0084] The conductive agent, binder, and additive can all be selected from the conductive agents, binders, and additives commonly used in the positive active material layer in the art, which will not be elaborated here.

[0085] Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector. The negative electrode current collector can be selected from conventional negative electrode current collectors used in the art, such as copper foil. The negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder, and additives.

[0086] Among them, the negative electrode active material can be selected from silicon, silicon carbon, SiOx (0<X<2), lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerene, graphene, coke, carbon fiber, boron and its derivatives (such as boron powder, boron oxide), aluminum and its derivatives (such as aluminum powder, lithium aluminum alloy), magnesium and its derivatives (such as magnesium, magnesium aluminum alloy), bismuth and its derivatives (such as bismuth, lithium bismuth alloy), nickel and its derivatives (such as nickel, lithium nickel alloy, lithium nickel nitride), silver and its derivatives (such as silver powder, lithium silver alloy), zinc and its derivatives (such as zinc powder, zinc lithium alloy, zinc nitride), titanium and its derivatives (such as titanium powder, lithium titanate, titanium dioxide, lithium titanium alloy, etc.), gallium and its derivatives (such as gallium, lithium gallium alloy), indium and its derivatives (such as indium powder, lithium indium alloy), tin and its derivatives (such as tin powder, stannous oxide, tin oxide, tin sulfate), lithium nitride, and copper nitride. One or more.

[0087] In a specific embodiment, the negative electrode active material layer has a gram capacity of ≥330 mAh / g, preferably a gram capacity of ≥500 mAh / g.

[0088] In a specific embodiment, the single-sided thickness of the above-mentioned negative electrode active material layer (the thickness of the negative electrode active material layer after rolling) is 20μm to 110μm, preferably 30μm to 60μm, such as 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 70μm, 90μm, 110μm, etc.

[0089] The preparation method of the battery of the present application can be prepared according to conventional methods in the art.

[0090] In a specific embodiment, first, positive and negative electrode sheets are prepared, wherein the preparation method of the positive electrode sheet comprises: mixing a positive electrode active material, a binder, a conductive agent, and an additive, adding a solvent (e.g., N-methylpyrrolidone), and stirring in a vacuum mixer until a positive electrode slurry with uniform fluidity is obtained, and then the positive electrode slurry is coated on one or both sides of a positive electrode current collector, and after drying at room temperature, the mixture is transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet. The preparation method of the negative electrode sheet comprises: mixing a negative electrode active material, a binder, a conductive agent, and an additive, adding a solvent (e.g., deionized water), and stirring in a vacuum mixer to obtain a negative electrode slurry, and then the negative electrode slurry is uniformly coated on one or both sides of a negative electrode current collector, and after drying at room temperature, the mixture is transferred to an oven for drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0091] The positive electrode sheet, separator and negative electrode sheet are stacked and assembled in sequence to obtain a battery cell, the battery cell is placed in an outer package, an electrolyte precursor liquid is added, and the battery is prepared after packaging, curing and other processes.

[0092] The battery provided in this application will be described in detail below with reference to specific embodiments.

[0093] Example 1

[0094] The preparation method of the battery provided in this embodiment is as follows:

[0095] 1) Preparation of positive electrode

[0096] The positive electrode active materials nickel cobalt manganese (811), polyvinylidene fluoride, and carbon nanotubes are mixed in a weight ratio of 97.4:2:0.6, N-methylpyrrolidone is added, and the mixture is stirred under a vacuum mixer to obtain a positive electrode slurry with a solid content of 65%; the positive electrode slurry is coated on both sides of an aluminum foil, dried at room temperature, and then transferred to a 90°C oven for drying for 10 hours, and then cold pressed and cut to obtain a positive electrode sheet.

[0097] 2) Preparation of negative electrode sheet

[0098] The negative electrode active materials graphite and silicon carbon, the binder polystyrene-butadiene rubber, the dispersant sodium carboxymethyl cellulose, and the conductive agent carbon nanotubes are mixed in a weight ratio of 80:15:4:0.5:0.5, deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry with a solid content of 36%; the negative electrode slurry is coated on both sides of the copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0099] 3) Preparation of electrolyte precursor solution

[0100] 4% ethylene glycol dimethacrylate, 0.04% tert-butyl perbenzoate, 31.96% ethyl methyl carbonate, 1% 2-oxo-1,3,2-dioxathiolane, 10% ethylene carbonate, 6% diethyl carbonate, 12% fluoroethylene carbonate, 30% propylene carbonate, and 5% 1,3,6-hexanetrinitrile are uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium bistrifluoromethylsulfonyl imide (9:1) are added to the transparent liquid and dissolved to obtain an electrolyte precursor solution with a lithium salt concentration of 1.35 mol / L.

[0101] 4) Battery assembly

[0102] The positive electrode sheet, the separator and the negative electrode sheet are stacked and assembled in sequence to obtain a battery cell, the battery cell is placed in an outer packaging, an electrolyte precursor solution is added, and after packaging, the battery including the electrolyte precursor solution is charged to 3.7V at a temperature of 40°C, a pressure of 3MPa, and a rate of 0.3C; then, the battery is charged to a cutoff voltage of 4.2V at a temperature of 90°C, a pressure of 3MPa, and a rate of 0.9C to obtain a battery.

[0103] The preparation methods of the batteries of Examples 2 to 9 and Comparative Examples 1 to 2 are basically the same as that of Example 1, except that the positive electrode slurry formulation, negative electrode slurry formulation, electrolyte precursor solution, and curing conditions are different. The specific differences are listed in Table 1.

[0104] Table 1

[0105] Test example

[0106] 1. Gas chromatography analysis

[0107] The capacity of the batteries provided in Examples 1-9 and Comparative Examples 1-2 was tested. Dimethyl carbonate was then injected into the batteries and sealed. After standing for 36 hours, the mixed liquid components inside the batteries were removed and subjected to gas chromatography analysis. The analysis conditions were as follows, and the analysis results are shown in Table 2-3.

[0108] Analytical conditions: Agilent 7820A gas chromatograph, Agilent HP-5 chromatographic column, mobile phase nitrogen (99.999%), inlet temperature 270°C; split ratio 60:1; split flow rate 60 ml / min; detector temperature 300°C; air flow rate 400 ml / min; hydrogen gas flow rate 40 ml / min; column oven temperature increased by 5°C / min to 260°C and maintained for 10 min; chromatography-grade acetonitrile was used, with a sample to acetonitrile ratio of 1:99 and an injection volume of 0.2 uL.

[0109] Table 2

[0110] Table 3

[0111] According to the gas chromatography analysis results provided in Table 2-3, in the gas chromatography analysis results provided in Comparative Example 1-2, the peak times are 3.16min, 4.92min, 6.63min, 10.01min, 10.72min and 29.55min, and no characteristic peaks appear at 3.65-4.50min or 4.95-6.50min.

[0112] 2. XRD test

[0113] After disassembling the batteries of Examples 1-9, the electrolytes were subjected to XRD testing at a test angle of 10°-90°. Based on the test results, the diffraction peaks and their half-peak widths appearing in the X-ray diffraction patterns of the electrolytes of Examples 1-9 are listed in Table 4.

[0114] Table 4

[0115] 3. Cycle test

[0116] The batteries provided in Examples 1-9 and Comparative Examples 1-2 were allowed to stand at 25°C ± 2°C for 1 min; discharged at 0.2C to the lower voltage limit; allowed to stand for 1 min; charged at 0.5C to the upper voltage limit, with a cut-off value of 0.05C; tested for the first time; allowed to stand at 25°C for 1 min; discharged at 0.5C to the lower voltage limit; allowed to stand for 1 min; charged at 0.5C to the upper voltage limit, with a cut-off value of 0.05C, and allowed to stand for 1 min; cycled a certain number of times, and calculated the capacity retention rate. The test results are shown in Table 5.

[0117] Table 5

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A battery, wherein: including electrolytes; Inject dimethyl carbonate into the battery, let it stand for 36 hours, take samples, and perform gas chromatography analysis on the liquid in the battery; Based on the capacity of the battery, the injection amount of dimethyl carbonate is not less than 2.5 g / Ah; In the gas chromatography analysis spectrum, there is a first characteristic peak at 3.65-4.50 min, and a second characteristic peak at 4.95-6.50 min.

2. The battery according to claim 1, wherein In the gas chromatography analysis spectrum, there is a first characteristic peak at 3.80-3.90 min, and a second characteristic peak at 5.40-5.50 min.

3. The battery according to claim 1 or 2, wherein: The ratio of the peak area of ​​the second characteristic peak to the peak area of ​​the first characteristic peak is greater than 1.

4. The battery according to any one of claims 1 to 3, wherein: The ratio of the peak area of ​​the second characteristic peak to the peak area of ​​the first characteristic peak is not greater than 3.

2.

5. The battery according to any one of claims 1 to 4, wherein: The electrolyte has M first diffraction peaks with a 2θ diffraction angle of x and N second diffraction peaks with a 2θ diffraction angle of y in an X-ray diffraction pattern, M≥1, N≥1; Among them, 10°≤x≤30°, 30°≤y≤50°; The sum of the half-peak widths of the M first diffraction peaks is a, and the sum of the half-peak widths of the N second diffraction peaks is b, wherein 1.1≤b / a≤3.

2.

6. The battery according to claim 5, wherein 1.1≤b / a≤1.5; Or, 2.1≤b / a≤2.

3.

7. The battery according to claim 5, wherein 1.1≤a≤1.5, 1.4≤b≤3.

6.

8. The battery according to claim 1, wherein The conductivity of the electrolyte is 4mS / cm-12mS / cm; Preferably, the conductivity of the electrolyte is 5 mS / cm-12 mS / cm.

9. The battery according to any one of claims 1 to 8, wherein: The electrolyte includes a polymer obtained by polymerizing a polymerized monomer, wherein the polymerized monomer includes a functional group, and the functional group includes at least two acrylate groups.

10. The battery according to claim 9, wherein The polymerizable monomer is selected from one or more of a difunctional monomer, a trifunctional monomer, a tetrafunctional monomer, and a hexafunctional monomer.

11. The battery according to claim 10, wherein The bifunctional monomer is one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, and ethoxylated bisphenol A diacrylate and its derivatives; and / or, the trifunctional monomer is one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, trimethylolpropane trimethacrylate and its derivatives; and / or, the tetrafunctional monomer is ethoxylated (5) pentaerythritol tetraacrylate and its derivatives; And / or, the hexafunctional monomer is dipentaerythritol hexaacrylate and its derivatives.

12. The battery according to claim 1, wherein The battery is prepared by a method comprising the following steps: The battery comprising the electrolyte precursor solution is charged to 3.7V at a temperature of 10°C to 40°C, a pressure of ≤3MPa, and a rate of ≤0.3C; subsequently, the battery is charged to a cut-off voltage of ≥4.0V at a temperature of 60°C to 90°C, a pressure of ≤3MPa, and a rate of ≤0.9C, to obtain the battery; The electrolyte precursor solution includes polymerizable monomers.

13. The battery according to claim 1, wherein The battery is a solid-state battery or a semi-solid-state battery.

14. The battery according to claim 1, wherein The electrolyte is a solid electrolyte or a semi-solid electrolyte.

15. The battery according to claim 1, wherein The battery is a semi-solid battery, and the electrolyte comprises a polymer and an electrolyte solution.

16. The battery according to claim 15, wherein The electrolyte comprises 0.5 wt % to 10 wt % of a polymer and 90 wt % to 99.5 wt % of an electrolyte.

17. The battery according to claim 15 or 16, wherein: The electrolyte includes a lithium salt and a non-aqueous organic solvent.

18. The battery according to claim 17, wherein The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bisfluorooxalatoborate, lithium bisfluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium difluorophosphate, lithium perchlorate, lithium bisfluorosulfonamide and lithium bistrifluoromethylsulfonyl imide; And / or, the non-aqueous organic solvent is selected from one or more of cyclic carbonates, linear carbonates, and linear carboxylates.

19. The battery according to any one of claims 1 to 18, wherein: It also includes a positive electrode sheet; the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution positive electrode material, lithium nickel cobalt oxide, lithium nickel titanium magnesium oxide, lithium nickel oxide, spinel lithium manganese oxide, nickel cobalt tungsten, lithium nickel manganese oxide, and sodium-containing lithium cobalt oxide.

20. The battery according to any one of claims 1 to 19, wherein: It also includes a negative electrode sheet; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes one or more of silicon, silicon carbon, SiOx, lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerenes, graphene, coke, carbon fiber, boron and its derivatives, aluminum and its derivatives, magnesium and its derivatives, bismuth and its derivatives, nickel and its derivatives, silver and its derivatives, zinc and its derivatives, titanium and its derivatives, gallium and its derivatives, indium and its derivatives, tin and its derivatives, lithium nitride, and copper nitride.

21. An electronic device, wherein: A battery comprising any one of claims 1 to 20.